CYBER HUMAN VALUES DISPLAYED BY UNIVERSITY STUDENTS IN ONLINE SOCIAL NETWORKING SITES: THE RELATIONSHIP OF CYBER HUMAN VALUES TO CYBERBULLYING AND CYBER VICTIMIZATION BEHAVIORS DISPLAYED - Durak, H. Yildiz (Iated-Int Assoc Technology Education & Development, 2019)
This study aims to analyze cyber human values displayed by the university students in social networking sites and relationship level of these values with regard to cyberbullying and cyber victimization behaviors. In line with this purpose, data were collected from 211 state university students in different grades and departments in 2018-2019 academic year by using personal information form and three different scales. Descriptive statistics and correlation were used to analyze the related data. As a result of this descriptive survey, it is found out that the perception of the participants towards cyber human values is in the mid-range. The results suggest that in terms of amiability sub-dimension, perception level of the participants is higher; however, it remains in the lower level in terms of tolerance when compared to the other sub-dimensions. At the end of the study, it is found out that there is an intermediate and negative relation between cyber human values and cyberbullying while there is lower-level and negative relation between cyber human values and cyber victimization.
13th International Technology, Education and Development Conference (INTED) -- MAR 11-13, 2019 -- Valencia, SPAIN
Keywords: Cyber Human Values; Cyber Bullying; Cyber Victimization; University Students